Inventarisasi Tumbuhan Obat Di Kawasan Hutan Kota Babakan Siliwangi Bandung - Salma Humairo; Tere Jessica Putri Pribadi; Ateng Supriyatna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Medicinal plants are plants whose leaves, stems and roots can be used as medicine. Some of these medicinal plants are used in traditional or alternative medicine in local communities. Apart from that, medicinal plants also have the advantage that they do not cause side effects and can be treated by family members themselves. The successful use of medicinal plants is greatly influenced by public knowledge about the benefits of each type of medicinal plant, especially medicinal plants that have been studied empirically. Research with the title Inventory of Medicinal Plants in the Babakan Siliawangi City Forest Area on June 12 2024, with this research method aims to determine the diversity of types of medicinal plants and to determine the potential of these medicinal plants for the surrounding community. The results of this research were 10 types of medicinal plants, including: Binahong, Yellow Bamboo, Jengkol, Matoa, Forest Tea, Forest Betel, Japanese Papaya, Sausage Tree, Butterfly Tree, Simpur Tree. The most widely used medicinal plant organ is the root, bark, flowers and leaves.